Determination of the Optimum Preload of Roller Bearings in Terms of their Life Using Fem - Slavomir Hrcek; Robert Kohar; Stefan Medvecky; Branislav Krchnavy; Marcel Caco (Communications - Scientific letters of the University of Zilina, 2016)
The objective of this paper is to describe the procedure of correct determination of the optimum preload of tapered roller bearings in terms of their fatigue life, using the procedure laid down in ISO 281, and by analysis of contact stress state (analytically and by the FEM) with application of the Lundberg-Palmgren theory. The procedures will be applied to a specific example of the fit of the output shaft of a gearbox in a pair of tapered roller bearings designed specifically for this application.